Momentary precipitants connecting stress and smoking lapse during a quit attempt - Cambron, Christopher (Health Psychol, 2019)
OBJECTIVE. Most attempts at smoking cessation are unsuccessful, and stress is frequently characterized both as a momentary precipitant of smoking lapse and a predictor of subsequent changes in other key precipitants of lapse. The current study examined longitudinal associations among stress, multiple precipitants of lapse, and lapse among smokers attempting to quit. METHODS. Ecological momentary assessments (EMAs) were gathered from a multi-ethnic, gender-balanced sample of 370 adults enrolled in a smoking cessation program. EMAs (N=32,563) assessed smoking lapse and precipitants of lapse including stress, negative affect, smoking urge, abstinence self-efficacy, motivation to quit, difficulty concentrating, coping outcome expectancies, and smoking outcome expectancies. A multilevel structural equation model simultaneously estimated within person paths from stress to multiple precipitants and subsequent smoking lapse. Indirect effects of stress to smoking lapse through precipitants were computed. RESULTS. Results indicated that increased stress was significantly associated with all precipitants of lapse consistent with a greater risk for lapse (i.e., increased negative affect, smoking urge, difficulty concentrating, and smoking outcome expectancies, and reduced abstinence self-efficacy, motivation to quit, and coping outcome expectancies). All precipitants were significantly associated with subsequent lapse. Indirect effects indicated that stress was uniquely connected to lapse through negative affect, smoking urge, abstinence self-efficacy, coping outcome expectancies, and smoking outcome expectancies. CONCLUSIONS. Results of this study highlight the broad importance of stress for smoking lapse during a quit attempt. Smoking cessation programs should pay close attention to the role of stress in exacerbating key precipitants of lapse to improve cessation success rates.